Integrasi Kompetensi Teknologi Informasi dan Komunikasi Guru Dalam Pembelajaran Berdasarkan Perspektif Siswa MAN 01 Pontianak - Egy Abdi; Indri Astuti (Kelompok Peneliti Muda Universitas Negeri Jakarta, 2022)
Information and Communication Technology (ICT) competence in teachers refers to the skills of teaching staff in utilizing and implementing technology outputs to present effective educational content in learning. The effectiveness of instructional practices in the classroom environment by teachers can be analyzed by capturing the perspectives of those who are included in the ongoing learning process, including students. This study used a quantitative descriptive method which aimed to describe the perspective of the representative 100 students of MAN 01 Pontianak who was the parties to the assessment of the mastery of ICT integration of MAN 01 Pontianak teachers in learning. It can be concluded that teachers at MAN 01 Pontianak have moderate ICT mastery competence as the dominating category fulfilled based on the scores obtained, which means that awareness will create communicative nuances by integrating technology output in the process of distributing information in the classroom realm classified as not optimal. This is reinforced by the findings related to most of the students' perspectives, which assessed that teachers at MAN 01 Pontianak have medium-scale ICT mastery competence, 72% of 100 students stated that, there were 18% of students from all respondents stated that the teacher's ICT mastery competence was low and only 10% of them actually think that the competence of teachers' ICT mastery in the research location is high.